A Comparative Analysis of the Performance of the Czech Excellence Award Winners - Pavel Adámek (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Split, Croatia, 6-8 September 2018, 2018)
The purpose of this paper is to assess whether the implementation of excellence approach in area of a total quality management (TQM) positively affects the financial performance of the Czech companies. This paper test whether the adoption of excellence model approach from European Foundation of Quality Management (EFQM) has the impact on companies in the monitored indicators of the level of excellence in the Czech Republic represented by the group of emerging countries. This study is based on information gathered through an extensive literature review using print media, research databases, and we employed the available reporting for awarded companies. We systemized the variables of business excellence with the higher impact on organizational performance. As an example was involved the Czech companies awarded in National Quality Award (NQA) in the area of excellence. The main findings of this study shows the positive relation in selected financial indicators after receiving NQA and implementation excellence approach. In terms of the Czech Republic, although the NQA system is in place, Czech companies are not so interested, even though they can get feedback and work on their approach within the set criteria of the EFQM model in NQA. Based on selected performance indicators, the positive development of the companies was demonstrated on performance achieved by the TQM-oriented award winning companies.
Keywords: M10; M11; M19; 330; EFQM Model Excellence; total quality management; emerging country; performance management